2012
DOI: 10.1111/j.1468-2494.2012.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Axillary skin: biology and care

Abstract: SynopsisIn skin care, the axilla is a biologically unique site requiring specialized attention and care. This area of skin is often subject to hair removal techniques, such as shaving and plucking. These procedures damage the skin leading to erythema and dryness in the short term, and in some cases, post-inflammatory hyperpigmentation (PIHP) in the long term. This study will (i) briefly review the biology and unique properties of axillary skin, and (ii) describe the characteristics of the irritation and damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…Visual assessments showed that hair removal by shaving, plucking and waxing leads to increases in axillary erythema and skin dryness scores. These results in Asian consumers are broadly consistent with earlier observations showing that hair removal results in axillary erythema and skin dryness in white subjects [4][5][6]. In the present study, shaving was associated with significantly less erythema but significantly greater skin dryness 30 min after hair removal compared with the other techniques.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Visual assessments showed that hair removal by shaving, plucking and waxing leads to increases in axillary erythema and skin dryness scores. These results in Asian consumers are broadly consistent with earlier observations showing that hair removal results in axillary erythema and skin dryness in white subjects [4][5][6]. In the present study, shaving was associated with significantly less erythema but significantly greater skin dryness 30 min after hair removal compared with the other techniques.…”
Section: Discussionsupporting
confidence: 93%
“…As far as we are aware, this is the first study to identify the principal cytokines associated with the inflammatory process triggered by axillary hair removal. This provides further details about the skin response step proposed in the axillary irritation cycle [6]. The results also suggest that buffer scrubs are a suitable technique (albeit with limitationssee below) for detecting some of the inflammatory response biomarkers associated with axillary irritation induced by hair removal.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Fatigue testing consists of small repetitive tensile force applied until the fibre fails. This is a more real‐world description of forces acting on hairs because real‐world breakage is messy, involving multiple forces (Figure ), but the long testing cycle duration and variability limits its utility. All conventional physical tests require long (>4 cm) fibres that have a homogeneous morphology and composition.…”
Section: Physics: the Hair Phenotype From Macro To Molecular Scalementioning
confidence: 99%